On the Dharma of Women: An analysis of Women and Ethics in the Hindu Epics - McDonald, Robert (University of Virginia, 2022)
This paper analyzes the complicated nature of Dharma as it relates to women in Hinduism. We are given a contrasting account of women in Hindu texts, in the legal and political treatises we see classical gender schemas of Patriarchy and female subordination. In the narrative works however, we see examples of women actively challenging men using the tools traditionally associated with masculinity (reason, argumentation, religious purity etc.). This paper attempts to navigate this discrepancy and explain how the contradictory representation of women can actually offer insight into the way gender was perceived and expressed in ancient India.
Original submission date: 2022-05-02T16:16:32Z
Keywords: Dharma; Mahabharata; Ramayana; Sita; Draupadi